2011
DOI: 10.1021/mp200026v
|View full text |Cite
|
Sign up to set email alerts
|

Vectorial Transport of Fexofenadine across Caco-2 Cells: Involvement of Apical Uptake and Basolateral Efflux Transporters

Abstract: Fexofenadine is a nonsedative antihistamine that exhibits good oral bioavailability despite its zwitterionic chemical structure and efflux by P-gp. Evidence exists that multiple uptake and efflux transporters play a role in hepatic disposition of fexofenadine. However, the roles of specific transporters and their interrelationship in intestinal absorption of this drug are unclear. This study was designed to elucidate vectorial absorptive transport of fexofenadine across Caco-2 cells involving specific apical u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 51 publications
3
58
0
1
Order By: Relevance
“…The potential involvement of a basolateral efflux transporter in the MRP family is supported by the observation that the addition of MK571 increased the efflux ratio in each of the cell lines lacking P-gp (up to 1.52 in the case of MDR1 KO cells). These data support the conclusions drawn by Ming et al (2011) that fexofenadine apical efflux in Caco-2 cells is predominantly mediated by P-gp, whereas basolateral efflux is predominantly mediated by MRP3. Based on data using MK571 and a P-gp/BCRP inhibitor (GW120918), Ming et al (2011) further suggested that MRP2 makes a small contribution to the apical efflux of fexofenadine, although our data using the MRP2 KO cell lines do not support the involvement of MRP2.…”
Section: Discussionsupporting
confidence: 91%
“…The potential involvement of a basolateral efflux transporter in the MRP family is supported by the observation that the addition of MK571 increased the efflux ratio in each of the cell lines lacking P-gp (up to 1.52 in the case of MDR1 KO cells). These data support the conclusions drawn by Ming et al (2011) that fexofenadine apical efflux in Caco-2 cells is predominantly mediated by P-gp, whereas basolateral efflux is predominantly mediated by MRP3. Based on data using MK571 and a P-gp/BCRP inhibitor (GW120918), Ming et al (2011) further suggested that MRP2 makes a small contribution to the apical efflux of fexofenadine, although our data using the MRP2 KO cell lines do not support the involvement of MRP2.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, in contrast to MDCK cells, Caco-2 failed to sort recombinant NTCP-GFP protein into polarized surface expression on the plasma membrane and showed no polarity of taurocholate uptake (Sun et al, 2001), thus suggesting a lack of meaningful NTCP protein expression and function in Caco-2 systems. Both OATP1A2 and OATP2B1 are expressed at the apical membrane of enterocytes or Caco-2 cells (Sai et al, 2006;Glaeser et al, 2007), where they can contribute to the absorption of drugs such as statins, fexofenadine, levofloxacin, methotrexate, and talinolol (Badagnani et al, 2006;Ho et al, 2006;Maeda et al, 2007;Kitamura et al, 2008;Shirasaka et al, 2010;Ming et al, 2011). For the aforementioned reasons, it is highly unlikely that OATP1B1, OATP1B3, OATP2B1, OATP1A2, or NTCP could be involved in the basolateral uptake of rosuvastatin in Caco-2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Kinetic analysis of rosuvastatin basolateral uptake in Caco-2 at 37°C was performed by nonlinear regression analysis using GraphPad Prism 5.0 (GraphPad Software Inc., San Diego, CA). The data were fit to a model containing a saturable and a nonsaturable term (Ming et al, 2011):…”
Section: Rosuvastatin Basolateral Transport In Caco-2 Cellsmentioning
confidence: 99%
“…OATP2B1, the study can be performed at a lower pH (pH 5-6.5) to optimize Pcar. [36,[41][42][43] However, introducing a pH-gradient may be complex when only the anionized form is the exclusive substrate for the transporter since the decreased concentration of this species may reduce Pcar. Consequently, the Km or Ki may appear pH-dependent.…”
Section: Influx Transportersmentioning
confidence: 99%
“…OATP2B1) may not be accounted for. [36,[41][42][43] Ideally, efflux ratios should be performed both in the presence and the absence of a pH-gradient. In the presence of a pH-gradient, the efflux ratios determined at a low and high concentration (high enough to saturate all transporters) of the ionizable drug substance could be compared to distinguish between transporter effects and pH-partition.…”
Section: Limitations Of In-vitro Determined Kinetic Parameters For Trmentioning
confidence: 99%